Representations and narrative functions of empathy in Milan Kundera's The Unbearable Lightness of Being - Robova, Antoaneta (Romanica Olomucensia, 2023)
Milan Kundera's novels are characterised by a strong intellectualisation of the narrative choices, which includes a very significant essayistic and (self-)reflexive component. The complex composition, irony, and polyphony encourage a slow approach on the part of the reader engaged in a cognitive quest. A recurrent textual strategy in Kundera's novels is to introduce a narrator into the world of fiction. The functioning of narrative empathy and the different representations of affective states are analysed in the novel The Unbearable Lightness of Being through the prism of cognitive literary studies and reception theory. Some narratological devices and approaches are also used to discuss the narrative functions of empathy. Representations of feelings from the spectrum of empathy and reflections on the concept of compassion are integrated into the novelistic fable. They become leitmotifs, capable of stimulating a response in the reader and of triggering affective empathy towards the characters. The reader's cognitive empathy is activated by the mediation of the narrator in this novel, which also thematises the manifestations of empathy and compassion by inserting them into the main storyline. Tomas's empathetic treatment of his partner Tereza functions as a turning point, revealing the existential ambiguity of personal choices. The narrator-mediator constructs the reader's mental image of the implied author and performs a function of activating cognitive empathy in the model reader. The extradiegetic voice provides metanarrative comments and contributes to the participatory involvement of the reader.
Keywords: Milan Kundera; narrative empathy; novel; irony; reception